Students Error Analysis In Using Past Continuous Tense - Marwati, sri (INTERACTION: Jurnal Pendidikan Bahasa, 2019)
The purpose of this study was to analyze the students’ error in using past continues tense. The specific objectives were to analyze kinds of error made by the students, to analyze the dominant kind of the students’ error and further more to found out their probably causes. In analyzing data, the writer were giving test to the students to measure the students’ results of their ability and analyze their cases in their study on using past continues tense. The writer took points in every student works, counted it and analyzed. This study were using quantitative descriptive research, in which include counted on analyzed and present the result of study by described on concluding it. The data took from the population of the second grade of SMP Muhammadiyah Aimas were include two class and the writer took the sample from12 (twelve) students from one class. The students of this study had been studied the theory of past continues tense before it. First step in collecting data the writer gave explanation related the theory of past continues tense to follow up the students’ memories in understanding, share the worksheet then explaining the instruction of the test before gave the test. By the observation to the students’ result test, she found four kinds of the students’ error with the frequency: error in addition= 53 (25, 24%), error in omission= 60 (28, 57%), error in miss-formation = 57(27, 14%), and error in miss-ordering = 40 (19, 05%) and the most dominant error was error in omission = 60 (28, 57%). The causes of error were classified based on the theory by John Norris (carelessness, first language interference, and translation), analyzed on the students’ results test.